Optimization of renewable energy-based electrical systems on tourist ships in Labuan Bajo - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah (Institute of Advanced Engineering and Science, 2025)
The use of fossil fuels on tourist boats in Labuan Bajo poses challenges in the form of high operational costs and significant environmental impacts. This study aims to optimize the renewable energy-based electrical system by utilizing a hybrid photovoltaic and generator system on tourist boats. The methods used include simulation and technical, economic, and socio-cultural analysis to evaluate the feasibility and efficiency of the system. The results of the study show that technically, the hybrid photovoltaic (PV)-generator system is able to improve energy efficiency and reliability of electricity supply, especially in dealing with fluctuations in power needs. From an economic aspect, this system has been proven to reduce fossil fuel consumption by up to 40%, which has an impact on long-term operational cost savings, even though the initial investment is quite high. Socio-culturally, the implementation of this system supports sustainability values and provides a positive image for the tourism industry in Labuan Bajo as an environmentally friendly destination. The use of a hybrid PV-generator system is an innovative and sustainable solution for tourist boats in Labuan Bajo, which not only improves technical efficiency and economic benefits but also supports environmental conservation and sustainability-based tourism.